Assessment of resistance level in tea red spider mite, Oligonychus coffeae against certain acaricides - Roobak Kumar, A.; Babu, A.; Sankara Rama Subramaniam, M.; Kumar, P. (Journal of Plantation Crops, 2012)
The level of resistance in red spider mite populations infesting tea to acaricides like, fenpropathrin, ethion and dicofol was assessed. Field collected red spider mites from three different tea growing regions of southern India were subjected to dose mortality studies to obtain the median lethal concentration of the acaricides and the resistance ratio of susceptible and resistant populations. The resistance ratio ranged from 1.96 to 2.13, 1.08 to 1.11 and 1.11 to 1.26 fold for fenpropathrin, ethion and dicofol, respectively. The general esterase activity with α - naphthyl acetate as substrate also showed increased activity (1.78 to 2.53 fold) in field collected populations than the laboratory reared mites (without exposing to any acaricides) for more than 20 generations. Esterase activity in Poly Acrylamide Gel Electrophoresis (PAGE) profile also indicated a higher level of resistance in mites collected from the Nilgiris region compared to that of Central Travancore and the Anamallais region.